Nature protection and sustainable tourism interaction in selected Ramsar Sites in Vojvodina (Northern Serbia) - Stojanović, Vladimir; Lazić, Lazar; Dunjić, Jelena (Geographica Pannonica, 2018)
This paper explores wetland-based tourism in four Ramsar sites in northern Serbian province Vojvodina, as well as a connection between tourism and nature protection. These regions are of great importance for Vojvodina, especially from the point of view of ecosystem services, because 83.3% of its territory are agricultural areas. Explored Ramsar sites were designated in period from 2004 to 2008 and they have been included in many plans as important areas for tourism development. However, the level of tourism development in these sites is not uniform because it depends on variety of factors such as touristic attractions value, engagement of nature protection managers in tourism development, and level of nature degradation and protection. The main objective of this paper is to determine the interconnection between nature degradation, nature protection and tourism development in selected Ramsar areas of Vojvodina, based on the Internal data of protected area managers,Report on the state of the environment and the scope of tourism development (infrastructure, services, development plans).
Keywords: Ramsar sites; Vojvodina; nature protection; sustainable development; ecotourism